Methods of teaching English language in primary school - Yunusova Barno Tulkunovna (Zien Journals, 2022)
This article introduces the use of scientific methods used for the formation of English language learning skills in young schoolchildren, to simplify the language learning process, and foreign experience in this regard.
Keywords: Common European Framework of Reference; previous research; proficiency; speaking in chorus